O GEOGEBRA 3D NA CONSTRUÇÃO DA PIRÂMIDE A PARTIR DE SEU TRONCO: REGISTROS DE REPRESENTAÇÃO SEMIÓTICA - Bettin, Anne Desconsi Hasselmann (2017)
The present work is the result of a research done with students of the third year at Polytechnic High School, a public state school. The aim of this research was to analyze the contents of pyramids through a generative problem, in order to analyze the mobilization of the Semiotic Representation Registers from the trunk of the pyramid with the use of 3D Geogebra. It emphasizes its qualitative and exploratory character, searching for relevant information through the analysis of the students' registers, both in the paper and in the use of Geogebra 3D software, in which mathematical concepts were represented in different forms of representation of the same mathematical object. The research was based on Duval's Registers of Semiotic Representations through the combination of diversified activities and the different registers of semiotic representations. The activities were divided into three stages, in which the student's previous knowledge was analyzed in stage I; In stage II, the student's records and reasoning with the manipulable material and, in stage III, the student's records and reasoning with the use of the Geogebra 3D software, which part of the understanding of the concrete material for the use of the technologies by middle of Geogebra 3D. The results showed that the proposed activities contributed to the revision of basic concepts of geometry, to the construction and comprehension of new concepts, in the visualization of the object in different forms of representation, where 3D Geogebra allowed to remember and to discover elementary concepts of flat and spatial geometry in a more attractive form, stimulating visualization and learning, showing a strong indication that the study of the pyramids attracted attention and was motivating for this construction.